Cohort Study on the Effect of Psychological Education for Nurses in Psychiatric Department. (25th August 2022) - Chu, Lifang; Qian, Guoying
Abstract : With the deepening of the medical and health system, high-quality nursing service with the reform of nursing service model and the provision of holistic nursing care for patients as the core connotation is being comprehensively carried out. With the continuous improvement of medical quality, people's awareness of health has gradually increased. They have put forward higher requirements for medical quality, nursing service quality, and medical care safety. Under the influence of these conditions, the workload and work pressure of clinical nurses continue to increase, and mental health problems become increasingly prominent. According to relevant data, the detection rate of occupational stress among nurses was 100%, and the proportion of nurses who perceived considerable stress was 60.9%, which seriously affected their work efficiency and quality of life. However, the physical and mental health of the frontline nurses working in psychiatric hospitals is not optimistic. This study explored the effects of psychological education among nurses in the department of psychiatry. The results showed that psychological education intervention among nurses in the department of psychiatry could alleviate their professional tiredness, effectively improve their psychological elasticity and happiness index, and thus improve sleep quality and promote their physical and mental health development.